Three dimensional evaluation of changes in maxillary sinuses and pharyngeal airway in class iii maxillary deficiency cases undergoing orthopedic facemask treatment - Pamporakis, Paschalis (My University, 2012)
Bu tezin başlığı: “Ortopedik Yüz Maskesi Tedavisi gören Sınıf III maksiller yetersizlik vakalarında sinus boşlukları ve farengeal havayolundaki değişikliklerin üç boyutlu değerlendirilmesi”. Bu çalışmanın amacı, büyümesi devam eden maksiller yetersizliğe bağlı sınıf III malokluzyona sahip yüz maskesi ile tedavi görmüş hastalarda tedavinin maksiller sinüsler ve farengeal hava yolu boşluğuna etkilerini incelemektir. Çalışmada 22 hasta kullanılmıştır. Çalışmadaki hastaların hepsinin ortalama yaşı 10`dur. Tüm hastalar normal ya da düşük yüz yüksekliğine, normal boyutta ve konumda alt çeneye ve yetersiz maksiller büyümeye sahiptir. Hastaların iskeletsel yaşı servikal büyüme yöntemine göre tayin edilmiştir. Tüm hastalar aktif büyüme periyodunun farklı aşamalarındadır. Tüm hastalara önce hyrax ekspansiyon vidası içeren akrilik splint yerleştirilmiş ve 7 gün süresince hastaların vidayı çevirmesi istenmiştir. Yedinci günde Petit tipi yüz maskesi tedavisine başlanmıştır. Yüz maskesi tedavisi yaklaşık 10 ay sürmüştür. Apereyler, yaklaşık 5 mm overjet ve sınıf II kanin ve molar ilişkisi elde edilince çıkarılmıştır. Retansiyon döneminde hastalar yaklaşık 3 ay süresince sınıf III bianatörü kullanmışlardır. Hacimsel değişiklikler tedavi başında ve yüz maskesi tedavisi sonunda alınan konik ışınlı bilgisayarlı tomografi görüntüleri ile ölçülmüştür. Çalışmanın sonucuna göre tedavi sonunda maksiller sinüslerin hacminde istatistiksel olarak anlamlı bir artış bulunmuştur. Ancak farengeal hava yolu boşluklarındaki hacimsel artış istatistiksel olarak anlamlı değildir. Maksiller sinüslerin ve hava yolu boşluklarının normal büyüme ve gelişimi hakkındaki literatürleri göz önüne alırsak yüz maskesi tedavisinin maksiller sinüslerin hacmini arttırmadığını, hatta farengeal hava yolu boşluğunun büyümesine engel olduğunu söyleyebiliriz. farengeal havayolu, maksiller sinüs, konik ışınlı bilgisayarlı tomografi, yüz maskesi.

The title of the present thesis is: “Three dimensional evaluation of changes in maxillary sinuses and pharyngeal airway in class III maxillary deficiency cases undergoing orthopedic facemask treatment”. The aim of this study was to assess short term alterations in the volume of maxillary sinuses and pharyngeal airway space (PAS), associated with facemask use in growing Class III maxillary deficient patients. . Twenty two patients were selected for treatment. Mean age for the study group was 10 years. All patients were diagnosed with normal or low vertical growth pattern, with maxillary deficiency and normal mandible. For each patient, hyrax expansion screw with acrylic cap splint was constructed and rapid palatal expansion was performed for 7 days. At the 7th day, protraction therapy with a Pettit type face mask started. The patients were treated with maxillary protraction therapy for an average period of 10 months. The appliance was removed when an overjet of 5mm and full Class II molar and canine relationship were achieved. Then patients were treated with a Class III bionator for retention, for a period of 3 months. Volumetric measurements were performed in order to reconstruct three-dimensional images and calculate the volume of the pharyngeal airway and the maxillary sinuses. The results showed a statistically significant increase in the volume of maxillary sinuses after treatment. On the other hand the increase in the volume of pharyngeal airway was not statistically significant. When we took into consideration the available in the literature dada concerning the normal growth of maxillary sinuses and pharyngeal airway, we reached the verdict that our treatment didn’t affect at all the volume of maxillary sinuses and actually inhibited the normal expected increase of the volume of pharynx. Key words: Pharyngeal airway, maxillary sinus, Cone Beam Computed Tomography, facemask treatment.
Keywords: Ortodonti